Aircraft accident in Brazil: Boeing vs. Legacy? - Almeida, Ildeberto Muniz de [UNESP]; Paraguay, A. I. B. B.; Reichmann, M. L. A. B. (Wit Press/computational Mechanics Publications, 2008)
Air accidents represent a small proportion of the flights registered worldwide. Airplane collisions in the air are rare. In September of 2006, a Boeing 737-800 collided in midair with a Legacy Jet. It was the largest accident registered in the history of Brazilian aviation until that time. The present study explores aspects of press coverage of the accident. Data and information reported in the media about the accident from September 2006 to August 2007 were collected and discussed. Media coverage called attention to two unusual aspects: politicisation of the discussion, culminating in the opening of congressional inquiries, and equally the concomitance of police investigations interfering in the work of agencies responsible for the official accident investigation. Emphasis on assigning guilt and establishing penalties may close the windows of opportunity an accident had opened for discussions on the improvement of air safety. In Brazil, political imperatives and organizational pressures have interfered and the possibilities of organizational learning from the accident have been drastically curtailed.
Keywords: air accident; investigation of accidents; conception of accidents; fatal accidents; causality; flight safety; safety system; air safety; Boeing; Legacy